An Integrated On-demand Technology for Pharmaceutical Drug Traceability in the US - Shambhu Sarkar (Advanced Concepts in Pharmaceutical Research Vol. 1, 2023)
Pharmaceutical serialization is a legal requirement that ensures each unit of prescribed medication is given a special identification number. In the supply chain, this unique identification is utilized for product tracking and authentication. To reduce the risk of fake medications entering the US market, the Drug Supply Chain Security Act (DSCSA) first introduced pharmaceutical drug serialization laws in 2018. A 2D data matrix barcode encoded with a unique identity must be printed on each drug unit by the pharmaceutical drug maker. Basically, the risk of drug counterfeiting cannot be completely eliminated by simply printing a special identifying code for authenticity and traceability on each prescription medicines. Therefore, by copying the identical information in numerous units, criminals and drug counterfeiters can still introduce unlawful or stolen medications into the supply chain through an illicit source or online commerce. We discovered that the US market lacked a technology to authenticate individual medicine units with a centralized, secure repository before dispensing them to patients. The United States ultimately requires a integrated on-demand technology where all approved trading partners to be connected for drug authentication. Before releasing medicines into the market, the manufacturer must update the product’s unique identifier in the centrally connected hub database. This procedure will guarantee that patients are receiving genuine medication and reduce the possibility of administering unauthorized or counterfeit pharmaceuticals.